Enhanced production of infectious particles by adaptive modulation of C-prM processing and C-C interaction during propagation of dengue pseudoinfectious virus in stable CprME-expressing cells - Sutha Sangiambut (2020)
Dengue virus assembly involves the encapsidation of genomic RNA by the capsid protein (C) and the acquisition of an envelope comprising the premembrane (prM) and envelope (E) glycoproteins. This rapid process, lacking in detectable nucleocapsid intermediates, may impose authentic C-prM-E arrangement as a prerequisite for efficient particle assembly. A mosquito cell-based complementation system was employed in this study to investigate the possibility that expression of the three structural proteins in trans allows the efficient production of a partially C-deleted dengue virus as compared to the presence of C alone. Following the transfection of ΔC56-capped RNA transcripts into C6/36 cells transiently expressing C or CprME, the production of the single-cycle virus was comparable. Subsequent propagation in the stable CprME-expressing clone, however, supported virus adaptation leading to acquisition of the L29P and S101F (PF) dual mutations in the C protein. The triple mutant, ΔC56(PF), exhibited enhanced levels of virus replication, specific infectivity and frequent increases of intracellular C dimer, as compared with ΔC56 in the CprME-clone. The PF mutations were associated with the accumulation of truncated CprM in ΔC56(PF)-infected cells, and uncleaved CprM as well as reduced intracellular C-dimer when the dual mutations were introduced into the wild-type dengue virus genetic background. These results indicate that the PF mutations may exert a replication-enhancing effect for the triple mutant virus by relieving the interference of trans-complementing structural proteins during viral assembly and suggest that the C-prM-E arrangement may be advantageous for pseudoinfectious virus production.